1997
DOI: 10.1183/09031936.97.10071535
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of influenza-like symptomatology and improvement of cell-mediated immunity with long-term N-acetylcysteine treatment

Abstract: N-acetylcysteine (NAC), an analogue and precursor of reduced glutathione, has been in clinical use for more than 30 yrs as a mucolytic drug. It has also been proposed for and/or used in the therapy and/or prevention of several respiratory diseases and of diseases involving an oxidative stress, in general. The objective of the present study was to evaluate the effect of long-term treatment with NAC on influenza and influenza-like episodes.A total of 262 subjects of both sexes (78% ≥65 yrs, and 62% suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 13 publications
3
116
0
6
Order By: Relevance
“…The authors concluded that NAC did not prevent influenza A (H1N1) virus infection, but did significantly reduce the incidence of clinically apparent disease [52]. In another paper, it has been reported that a patient with viral pneumonia caused by the novel influenza A (H1N1) virus 2009 infection and septic shock improved rapidly after continuous intravenous infusion of high-dose NAC at 100 mg/kg combined with oseltamivir [53].…”
Section: Superoxide Dismutasesmentioning
confidence: 95%
“…The authors concluded that NAC did not prevent influenza A (H1N1) virus infection, but did significantly reduce the incidence of clinically apparent disease [52]. In another paper, it has been reported that a patient with viral pneumonia caused by the novel influenza A (H1N1) virus 2009 infection and septic shock improved rapidly after continuous intravenous infusion of high-dose NAC at 100 mg/kg combined with oseltamivir [53].…”
Section: Superoxide Dismutasesmentioning
confidence: 95%
“…NAC stimulates glutathione synthesis and scavenges free radicals. 11 This compound is taken up by N-deacetylase, hydrolyzed to form cysteine and is used for glutathione synthesis. 12 Afterwards, glutathione peroxidase enzyme family, particularly glutathione peroxidase-1, utilizes glutathione to protect cells from oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…NAC freatinent is correlated with an increase in T cell immunity (Breithaupt et al, 1996;Droge, Eck, and Mihm, 1992;Wu, Levy, and Black, 1989) and may provide therapeutic benefit for a wide range of diseases (Beloqui et al, 1993;Bengtsson et al, 2001;De Flora, Grassi, and Carati, 1997;Walters et al, 1986) possibly by modulating immune response. Intravenous adminisfration of large doses of NAC as an antidote for acetaminophen poisoning can cause anaphylactic responses in sensitive individuals (Lifshitz, Kommehl, and Reuveni, 2000;Reynard, Riley, and Walker, 1992) most likely due to histamine release (Lifshitz, Kommehl, and Reuveni, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Acute side-effects reported in association with NAC administration range from gastrointestinal upset, vomiting, and fatigue to anaphylactic and allergic reactions (Bobb, Arfsten, and Jederberg, 2004;Pendyala et al, 2001;Pendyala and Creaven, 1995;Tenenbein, 1984;Ziment, 1988). Several studies have reported on the sideeffects in patients administered high doses of NAC (De Flora, Grassi, and Carati, 1997;De Rosa et al, 2000;Lifshitz, Kommehl, and Reuveni, 2000;Pendyala et al, 2001;Pendyala and Creaven, 1995;van Zandwijk et al, 2000), but the subject populations in most of these studies are patients with serious medical conditions. Therefore, the symptoms reported m these studies may not represent side-effects expected to occur in healthy populations under similar dosing regimens.…”
Section: Introductionmentioning
confidence: 99%